Distant Symmetry Control in Electron-Induced Bond Cleavage - Ragesh Kumar, T P; Nag, P; Ranković, M; Luxford, T F M; Kočišek, J; Mašín, Z; Fedor, J (The journal of physical chemistry letters, 2022)
We experimentally show that N-H bond cleavage in the pyrrole molecule following resonant electron attachment is allowed and controlled by the motion of the atoms which are not dissociating, namely, of the carbon-attached hydrogen atoms. We use this fact to steer the efficiency of this bond cleavage. In order to interpret the experimental findings, we have developed a method for locating all resonant and virtual states of an electron-molecule system in the complex plane, based on all-electron R-matrix scattering calculations. Mapping these as a function of molecular geometry allows us to separate two contributing dissociation mechanisms: a π* resonance formation inducing strong bending deformations and a nonresonant σ* mechanism originating in a virtual state. The coupling between the two mechanisms is enabled by the out-of-plane motion of the C-H bonds, and we show that it must happen on an ultrafast (few fs) time scale.